(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Setting: Department of otolaryngology and Head-Neck surgery, Rajshahi Medical College Hospital, Rajshahi. Methods: 80 patients were included in this study during a period of July 2006 to June 2007. Study based on history, clinical, radiological, laboratory and histopathological examination. The larynx is divided for purpose of tumour classification into three regions- Supraglottic, Glottic and Subglottic. Results: The age ranges from 25 to 85 years. The overall male to female ratio 93.75:6.25. Laryngeal carcinoma shows significant association with low socioeconomic and education group. The commonest symptoms of laryngeal carcinoma was change of voice 100%(20) in case of glottic carcinoma and 90%(54)in cases of supraglottic carcinoma.Other common symptoms were difficulty of swallowing, respiratory distress, cough, neck swelling, haemoptysis, neck pain. Palpable cervical lymph node was present in 50% (40) cases Conclusion: Predominant histological type was squamous cell carcinoma 97.5%(78), undifferentiated carcinoma 1.25%(1), adenocarcinoma 1.25%(1). Symptoms of presentation has a significant association with site of involvement. The symptoms of presentation of supraglottic carcinoma occurred more frequently at the advanced stage. Bangladesh J Otorhinolaryngol; April 2020; 26(1): 37-40